Gaya Kepemimpinan Pengelola Mal Pelayanan Publik Kota Pekanbaru - Said Jamaluddin Syaputra; Sujianto Sujianto; Dadang Mashur (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This research is motivated by the leadership style applied at the Pekanbaru City Public Service Mall, where the leadership style exercised by the Head of the Pekanbaru City One-Stop Integrated Service Investment Service The Public Service Mall has managed to get an award that can be maintained for three consecutive years. The purpose of this study was to determine the leadership style adopted by the Head of the Pekanbaru One Stop Service Investment Service and to see the supporting factors for the success of this leadership style. This study uses Robbins' theory (2015) which explains that there are 4 leadership styles namely, directive leadership style, supportive leadership style, participatory leadership style, and achievement-oriented leadership style. This study used qualitative research using interview, observation, and documentation techniques at the Pekanbaru City Public Service Mall. The results of the study show that the leadership style used in managing the Pekanbaru City Public Service Mall has been successful in its implementation due to the results obtained in managing the public service mall which has received awards for three consecutive years. Supporting factors in the application of leadership style at the Pekanbaru City Public Service Mall are the existence of standard rules in work, qualified human resources and adequate service innovation. With these supporting factors, the Pekanbaru City public service mall won the award for three consecutive years.